QUANTITATIVE ANALYSIS OF THE EVOLUTION OF THE ORDER PELTASPERMALES (GYMNOSPERMS) - Markov A.V.; Naugolnykh S.V. (My University, 1998)
Similar phases are recognized in the evolution of the artificial (based on foliage or fructifications) taxa of peltasperms and of the "natural" taxa of marine invertebrates. Apparently, this is due to the fact that in common with groups of closely related "natural" taxa, plants with similar foliage (or fructifications) may form compact ecological groups and occupy similar niches. Similar phases in the evolution of foliage and fructifications of peltasperms did not occur synchronously. This was possibly related to the different ecological significance of these structures.